The role of tumour infiltrating mast cells (TIM) in gastric carcinoma remains an enigma : Clinicopathological correlation of mast cell density - Dr. C.D. Anand; Dr. G. Shivashekar; Dr. Muthu Sudalaimuthu; Dr. Amitkumar Kalaivani; Dr. A. Sundaram (Tropical Journal of Pathology and Microbiology, 2019)
Background: Tumour infiltrating mast cells (TIM) may have pro-tumorigenic and anti-tumorigenic roles based on the mediators released and the outcome of that balance at any given stage could determine the net effect on the progression of the cancer.Their pro-tumorigenic role has been documented in many cancers including prostatic cancer and a beneficial role in breast cancer. Their exact role in gastric cancer is still not very clear. Hence the present study was undertaken to make an attempt to infer the role of tumour infiltrating mast cells in gastric carcinoma by measuring mast cell density and correlating with clinicopathological parameters. Methods: Tissue from fifty one cases of gastric carcinoma were analysed and routine histological findings were recorded. Mast cells were clearly demonstrated in tissue using Toluidine Blue stain at pH 2.3. Mast cells were counted in the tumour tissue using an eyepiece grid and expressed as no. of cells / per sq. mm, i.e., mast cell density (MCD). Statistical correlation of the mean Mast cell density (MCD) to clinical parameters like age, gender, location of lesion and pathological parameters like histologic type, grade, depth of invasion, lymph node status were analysed for statistical significance. Results: MCD was statistically significantly higher (Mean MCD +/- S.D:3.48 +/- 2.31) in patient group above 60 years of age compared to patient group below 60 years. MCDwas statistically significantly increased in well differentiated adenocarcinoma (Mean MCD +/- S.D: 7.2 +/- 3.55) stomach compared to moderately differentiated adenocarcinoma and poorly differentiated adenocarcinoma. However, no significant difference in MCD was observed in primary gastric tumour tissue in cases with metastatic deposits in regional lymph nodes and cases without lymph node metastasis. Conclusions: Our results indicate that the role of mast cells in gastric carcinoma could be pro-tumorigenic in the early stages especially during angiogenesis with an increase in MCD in well differentiated tumours and a relative decrease of mast cells in higher histological grades. The absence of any significant difference of MCD in lymph node positive (for metastatic deposit) and lymph node negative group may indirectly indicate no significant role in later stages of the cancer. These results indirectly show that a balance between pro-tumorigenic and anti-tumorigenic factors is involved in the pathogenesis and progression of gastric carcinoma. The role of mast cells in inflammatory and ulcerative gastric lesions which could be precursor lesions to gastric carcinoma also needs to be considered.